Os direitos humanos como eixo na soberania estatal contemporânea - Zanon, Pedro Henrique Nascimento (2014)
Discussions on State Sovereignty gain prominence as one advances in the XXI century, since many social paradigms state conflict. The discourse of State Sovereignty promotes expulsion of foreign interference in the territory and state policy, but this speech is also able to cover up human rights violations. The goal of this research is to elaborate on the relationship between sovereignty and human rights, from a phenomenological approach and horizon in the following research problem: what is the power of interference of human rights in the provision of State Sovereignty? The results lead to the realization that the global system of human rights protection, designed after the Universal Declaration of Human Rights of 1948, gives the rules of the status of human rights above state, which would exclude the discretion of the State to determine its position in domestic law. The application of standards on Human Rights was set up in status above the norms of domestic law, since his tutelage can be pleaded in International Tribunals, both by states and by other subjects of international law. That is, this application would result, thus interfering Human Rights on state sovereignty.